Performance of Muhammadiyah Hospital as Social Entrepreneurship Organization: The Role of Leadership Effectiveness - Indra Nur Fauzi; Fendy Suhariadi; Albertus Eka Putra Hariyanto; Erlyn Yuly Astuti (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Background: Muhammadiyah is one of the largest religious organizations in Indonesia which owns and manages the largest non-profit hospitals for more than a hundred years. Muhammadiyah Hospital is a model of social entrepreneurship organization (SEO). Studies related to the performance of Muhammadiyah hospital organizations and their relationship with several other related variables have not been widely conducted and have focused more on Muhammadiyah's philanthropic activities and roles, Muhammadiyah's history in the field of health services, and the ethics of Muhammadiyah's health service. Therefore, this research aims to explore the relationship of variables Servant Leadership, Managerial Cognitive Capability, and Emotional Regulation to shape Organizational Performance (OP) with intermediate variable: Leadership Effectiveness in Muhammadiyah Hospitals. This research utilizes primary data which was collected through phone-call surveys with 443 top and middle management respondents at 111 Muhammadiyah Hospitals in Indonesia. The data was collected by trained and experienced Enumerators using structured questionnaire designed specifically for each type of respondents. Methods: The study utilizes Structural Equation Modelling (SEM) methods using Maximum Likelihood Estimation. The method is used to analyze the influence of variables Servant Leadership, Managerial Cognitive Capability, and Emotional Regulation: Improving and Worsening (IMP and WOR) on Organizational Performance (OP) with Leadership Effectiveness as a mediator. Results: The study results found that Servant Leadership, Managerial Cognitive Capability, and Emotional Regulation: Improving (IMP) have a positive effect on Leadership Effectiveness. The increasing Servant Leadership, Managerial Cognitive Capability, and Emotional Regulation: Improving (IMP) will increase Leadership Effectiveness. Meanwhile, Emotional Regulation: Worsening (WOR) has a negative effect on Leadership Effectiveness. Increasing Emotional Regulation: Worsening (WOR) will reduce Leadership Effectiveness. The analysis results show that Leadership Effectiveness variable directly affects Organization Performance positively, in terms of the effect of Leadership Effectiveness as a mediate variable. Conclusion:This research concludes that leadership effectiveness play an important role in the cognitive abilities of hospital directors in driving hospital performance and the hospital director's cognitive ability is the key to strengthen leadership effectiveness. Considering limitations of this research, future studies should employ a-mix method of quantitative and qualitative data collection technique to bring deeper analysis results, as well as include diverse leadership types other than servant leadership to explore their relationship with the organization performance.